A new approach to solving the time-cost trade-off problem based on the genetic algorithm and fuzzy theory - Pour, Nasser Shahsavari; Ghamginzadeh, Arman; Pour Kheradmand, Mansoor (International Journal of Engineering and Technology, 2012)
Time and cost are two important and controllable objectives in project structures which are considerably dependent on each other. Recently, beneficiaries’ demands for cost and time reduction in completing a project have been increased. This study proposes a new method for time-cost trade off problem (TCTP) in uncertainty condition. To solve the model a multi objective genetic algorithm has been integrated with fuzzy theory. Efficiency of this algorithm is demonstrated through an existing case example from the literature. Finally to make the algorithm more efficient the existing parameters in the model have been set through Taguchi method.